Lactate Dehydrogenase A or B Knockdown Reduces Lactate Production and Inhibits Breast Cancer Cell Motility in vitro - Khajah, Maitham A.; Khushaish, Sarah; Luqmani, Yunus A. (Frontiers in Pharmacology, 2021)
Background: Lactate dehydrogenase (LDH) plays an important role in cancer pathogenesis and enhanced expression/activity of this enzyme has been correlated with poor prognosis. In this study we determined the expression profile of LDH-A and B in normal as well as in endocrine-resistant and –responsive breast cancer cells and the effect of their knockdown on LDH activity, lactate production, proliferation and cell motility. Methods: knockdown experiments were performed using siRNA and shRNA. The expression profile of LDH and signaling molecules was determined using PCR and western blotting. Intra- and extra-cellular LDH activity and lactate levels were measured by a biochemical assay. Cell motility was determined using wound healing and agarose assays, while proliferation was determined using MTT assay. Results: LDH-A was expressed in all of the tested cell lines, while LDH-B was specifically expressed only in normal and endocrine-resistant breast cancer cells. This was correlated with significantly enhanced LDH activity and lactate production in endocrine resistant breast cancer cells when compared to normal or endocrine responsive cancer cells. LDH-A or –B knockdown significantly reduced LDH activity and lactate production, which led to reduced cell motility. Exogenous lactate or pyruvate supplementation enhanced cell motility co-incident with enhanced phosphorylation of ERK1/2. Conclusions: Enhanced cell motility in endocrine resistant breast cancer cells is at least in part mediated by enhanced extracellular lactate levels, and LDH inhibition might be a promising therapeutic target to inhibit cancer cell motility.